2017
DOI: 10.1038/modpathol.2016.192
|View full text |Cite
|
Sign up to set email alerts
|

Applications of molecular testing in surgical pathology of the head and neck

Abstract: Molecular testing in routine surgical pathology is becoming an important component of the workup of many different types of tumors. In fact, in some organ systems, guidelines now suggest that the standard of care is to obtain specific molecular panels for tumor classification and/or therapeutic planning. In the head and neck, clinically applicable molecular tests are not as abundant as in other organ systems. Most current head and neck biomarkers are utilized for diagnosis rather than as companion diagnostic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 90 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Similarly, organotypic slices as an alternative tissue culture can provide a longer culture time ( e.g. , up to 14 days); however, the organotypic slices typically deviate from the physiological state during long-term culturing. , In addition, fast labeling and imaging of sialoglycans in acute brain slices may find applications in surgical pathological analysis on tissues from patients during surgery to help with disease diagnosis and treatment. , …”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, organotypic slices as an alternative tissue culture can provide a longer culture time ( e.g. , up to 14 days); however, the organotypic slices typically deviate from the physiological state during long-term culturing. , In addition, fast labeling and imaging of sialoglycans in acute brain slices may find applications in surgical pathological analysis on tissues from patients during surgery to help with disease diagnosis and treatment. , …”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…50,51 In addition, fast labeling and imaging of sialoglycans in acute brain slices may find applications in surgical pathological analysis on tissues from patients during surgery to help with disease diagnosis and treatment. 52,53 In addition to acute brain slices, fMGL should generally be appliable to tissue slices from various organs other than the brain. Furthermore, the azido analogs of ManNAc-6-P should be evaluated in vivo (e.g., in living mice) in the future, which may lead to faster and/or more efficient in vivo labeling.…”
Section: ■ Conclusion and Discussionmentioning
confidence: 99%
“…In general, molecular pathology is defined as the assessment of nucleic acids and proteins to diagnose diseases, select treatment, and predict the prognosis [7].…”
Section: Molecular Pathologymentioning
confidence: 99%
“…The application of molecular [13], which aid pathologists in developing classification systems for diseases and providing correct and exact diagnoses. For instance, the implementation of PCR and FISH in routine testing has become essential for a long list of genetic alterations that are associated with tumors such as hematopoietic tumors, CNS tumors, and sarcomas [7] [14] [15]. For instance, it was reported that many oligodendroglial tumors present with loss of heterozygosity and co-deletion of 1p19q [16] [17], and this alteration becomes important in the diagnosis of this type of diffuse gliomas.…”
Section: Molecular Pathologymentioning
confidence: 99%